Increase in efficiency of quality and hole-making in glass-reinforced titanium laminate by reducing drilling vibroactivity - Sergey N. Shevtsov; Vladimir V. Sibirskiy; Evgeny G. Chigrinets (Advanced Engineering Research, 2016)
The work objective is to study the impact of the drill design value and geometrics on the quality of the processed holes, the efficiency, and the machining dynamics of the high-strength polymer composite - fiberglass plastic reinforced by titanium foil. Packs of the reinforcing layers made from the titanium foil or carbon fiber tapes are often used in the highly-loaded polymer composite structures. Processing in several operations and the application of sharp-ground tools provide the required dimensional accuracy, the surface macro- and microgeometry of the hole, and allow avoiding the delamination. The process of drilling fiberglass laminates under different patterns of HSS drills sharpening is studied. The data obtained allow determining the optimum type of instrument and operation mode taking into account the dependence of the high-altitude roughness parameters, the nature and amount of delamination in the entry (exit point) of the drill. The vibroactivity of the drilling process and its relationship with the quality metrics are studied using the computer-aided torque-sensing system. Some proposals for improving the hole-making technology applying to the glass-fiber spars of the main and tail helicopter rotors are developed.